PENDEKATAN KONSELING RATIONAL EMOTIVE BEHAVIOR THERAPY UNTUK MENGATASI MOTIVASI BELAJAR YANG RENDAH PADA PESERTA DIDIK SMA NEGERI 1 NALUMSARI - Zannah, Siti Mistaqul; Kusmanto, Agung Slamet; Sucipto, Sucipto (Jurnal Muria Research Guidance and Counseling (MRGC), 2023)
The purpose of this research is to overcome low learning motivation using a rational emotive behavior therapy approach. In this study the technique of providing Rational Emotive Behavior Therapy (REBT) counseling assistance is the reinforcement technique. The type of research used in this research is quantitative research designed to use quasi experiments. The researcher used a pretest and posttest design which was carried out at SMA Negeri 1 Nalumsari. The results of the test calculations obtained an Asymp.Sig (2-tailed) value of 0.020 0.05, so it can be concluded that the hypothesis is accepted. Thus, it means that the difference in the pretest and posttest scores is significant, meaning that there is a significant difference between the scores of learning motivation before and after being given treatment in other words Ha is accepted, which means that positive reinforcement can be used to overcome low learning motivation in students of SMA Negeri 1 Nalumsari class XIIPS 2. In this research, teachers should be able to apply a rational emotive behavior therapy counseling approach to overcome low learning motivation.